Splines in Higher Order TV Regularization - Steidl, Gabriele; Didas, Stephan; Neumann, Julia (International journal of computer vision, 2006)
Issue Title: Special Issue: The 5th International Conference on Scale-Space and PDE Methods in Computer Vision Splines play an important role as solutions of various interpolation and approximation problems that minimize special functionals in some smoothness spaces. In this paper, we show in a strictly discrete setting that splines of degree m-1 solve also a minimization problem with quadratic data term and m-th order total variation (TV) regularization term. In contrast to problems with quadratic regularization terms involving m-th order derivatives, the spline knots are not known in advance but depend on the input data and the regularization parameter λ. More precisely, the spline knots are determined by the contact points of the m-th discrete antiderivative of the solution with the tube of width 2λ around the m-th discrete antiderivative of the input data. We point out that the dual formulation of our minimization problem can be considered as support vector regression problem in the discrete counterpart of the Sobolev space W ^sub 2,0^ ^sup m^. From this point of view, the solution of our minimization problem has a sparse representation in terms of discrete fundamental splines.[PUBLICATION ABSTRACT]